PENGARUH PENDIDIKAN KARAKTER DAN PEMBERIAN TUGAS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MARKETING KELAS XI JURUSAN PEMASARAN DI SMK NEGERI 7 MEDAN TAHUN AJARAN 2024/2025 - Farhana Irbah Lutfi Anisa; Ivo Selvia Agusti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of character education and assignment provision on student learning outcomes in the Marketing subject for class XI Marketing Department at SMK Negeri 7 Medan in the 2024/2025 academic year. This study uses an ex post facto research type with a quantitative approach. The population in this study amounted to 65 students, all of whom were sampled using total sampling technique. Data collection techniques used questionnaires with a Likert scale and documentation of Final Semester Examination scores. Instrument testing included validity testing using Pearson Product Moment correlation and reliability testing using Cronbach's Alpha. Data analysis technique used multiple linear regression analysis. The results showed that character education has a significant effect on student learning outcomes with tcount > namely 3,707 > 1.999 and a significance of 0.000 < 0.05. Assignment provision has a significant effect on student learning outcomes with tcont > ttable namely 2,174 > 1.999and a significance of 0.034 < 0.05. Furthermore, character education and assignment provision simultaneously have a significant effect on student learning outcomes with Fcount > Ftable namely56,470 > 3,145 and a significance of 0.000 < 0.05. The coefficient of determination (R²) of 0.646 indicates that 64.6% of the variation in learning outcomes can be explained by these two variables. Thus, the better the character education and assignment provision applied, the higher the student learning outcomes.